2020
DOI: 10.1002/ijc.33192
|View full text |Cite
|
Sign up to set email alerts
|

Cellular heterogeneity landscape in laryngeal squamous cell carcinoma

Abstract: Laryngeal squamous cell carcinoma (LSCC) is a highly malignant tumor originated from respiratory system. Although there have been many improvements in therapy until now, reducing the high mortality remains difficult. Understanding the cellular heterogeneity of LSCC could contribute to improve this problem. Single-cell RNA sequencing was applied to dissect the cell composition and molecular characteristics of LSCC tissues. Immunohistochemistry staining of the LSCC tissues was performed to identify the spatial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…Then immune cells and tumor cells were separately grouped and annotated based on the cell signature marker 17 . Data processing and analysis were performed as previously described 18 …”
Section: Methodsmentioning
confidence: 99%
“…Then immune cells and tumor cells were separately grouped and annotated based on the cell signature marker 17 . Data processing and analysis were performed as previously described 18 …”
Section: Methodsmentioning
confidence: 99%
“…The study of tumor cell heterogeneity allows for better understandings of tumor progression [101]. Laryngeal cancer single-cell data was clustered by pRS genes and fibroblasts associated with poor prognosis were postulated in this research.…”
Section: Discussionmentioning
confidence: 97%
“…Laryngeal cancer single-cell data was clustered by pRS genes and fibroblasts associated with poor prognosis were postulated in this research. Malignant proliferating cells and fibroblasts share the tumor margin in laryngeal cancer [101]. Numerous previous studies have confirmed that fibroblasts are one of the major components of TME and can establish dangerous associations with other TME cells, thereby creating a tumor-supporting environment in laryngeal cancer [102].…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been clarified that environmental carcinogens can induce damage of DNA and cause genomic irregularity [35][36][37][38][39][40]. Knowing that most LSCC patients are heavy smokers and alcohol consumers, studies analysing the molecular landscape and heterogeneity of LSCC, based on genetic alterations, could contribute to better understanding of the pathogenesis of this disease [7].…”
Section: Snp Selectionmentioning
confidence: 99%
“…Additionally, the lack of screening programs (endoscopic laryngeal examination performed by an otorhinolaryngologist) results in a delayed diagnosis of LSCC [6]. Hence, a better understanding of LSCC cellular heterogeneity could contribute to improving early diagnostics and survival rates of LSCC patients [7]. To find new blood-or 2 of 16 tissue-based biomarkers and to assess their association with the morphological and clinical manifestations of LSCC, recent research has focused on the role of genetic susceptibility factors as single nucleotide polymorphisms in carcinogenesis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%